Traumatic Macular Hole: Clinical Management and Optical Coherence Tomography Features. (20th October 2020) - Lei, Chunling; Chen, Li
Abstract : The complex and uncertain prognosis of traumatic macular hole (TMH) makes it a difficult and challenging problem in clinical management. The features of spontaneously closed TMH and the time of vitrectomy remain unclear. This retrospective study aimed to demonstrate the optical coherence tomography (OCT) features of TMH, explore the relationship between OCT parameters and visual outcomes, and further evaluate the therapeutic effect of surgical management. Seventeen TMH patients were included in this study. 13 eyes of TMH received vitrectomy surgery and 4 eyes of TMH were closed spontaneously. Baseline patient characteristics, surgical details, and 6-month postoperative follow-up clinical assessment were recorded prospectively. There was a moderate rate (4/17 eyes, 23.5%) of spontaneous closure. The mean time of hole closure was 9.5 ± 9.9 weeks, and 75% occurred within three months. In the spontaneously closed TMH eyes ( n = 4), an intact ellipsoid band was observed in all four patients with a mean age of 12.0 ± 1.6 years and a smaller preoperative basal diameter of 418.0 ± 283.6 μ m. Small basal diameter of the macular hole at baseline (p = 0.02) was associated with spontaneous closure of TMH acuity. In the vitrectomy surgery group ( n = 13), an intact ellipsoid band was observed in four patients (4/13) with a mean age of 27.0 ± 12.7 years and a larger preoperative basal diameter of 943.0 ± 444.2 μ m (p = 0.02). Vitrectomy results in a better closure rate (11/13 eyes, 84.6%). Combined with the spontaneously closed TMH eyes, the overall hole closure rate was 88.2% (15/17 eyes). After 6-month treatment for all patients, the best-corrected visual acuity (BCVA) increased to 0.59 ± 0.40 (logMAR) compared to baseline 1.01 ± 0.50 (logMAR) (p < 0.001). The ellipsoid band integrity was found to be closely correlated with visual acuity (p = 0.03). In conclusion, vitrectomy is an effective treatment for TMH. Surgical management for TMH achieved better anatomical closure and improved visual outcomes. Observation for 3 months may be considered before deciding if surgical intervention is suitable.